1996
DOI: 10.1074/jbc.271.12.6881
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the Lung-specific Surfactant Protein C Gene Is Mediated by Thyroid Transcription Factor 1

Abstract: Surfactant protein C (SP-C) is expressed in alveolar Type II epithelial cells of the lung. In order to determine the mechanism(s) that regulate gene transcription, we have analyzed the activation of the murine SP-C promoter in mouse lung epithelial cells (MLE cells) and in HeLa cells after co-transfection with a vector expressing rat thyroid transcription factor-1 (TTF-1). TTF-1 transactivated SP-C-chloramphenicol acetyltransferase constructs containing -13 kilobase pairs to -320 base pairs (bp) of the 5 flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(176 citation statements)
references
References 29 publications
12
163
1
Order By: Relevance
“…For transfection experiments, cells were seeded at 2x10 5 cells/well in six-well plates (TPP, Trasadingen, Switzerland) 24 h before transfection and transiently co-transfected using lipofectin (Invitrogen, Carlsbad, CA) with 3 ÎŒg of reporter plasmid, either SP-B luciferase [Yan et al, 1995] or SP-C luciferase plasmid [Kelly et al, 1996]; 2 ÎŒg of mock vector pcDNA3; and wild-type NKX2-1 or mutated NKX2-1 as specified in the figure legends. The cells were co-transfected with pRL-TK (Promega, Madison, WI) to normalize cell transfection efficiency.…”
Section: Cell Culture and Transactivation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For transfection experiments, cells were seeded at 2x10 5 cells/well in six-well plates (TPP, Trasadingen, Switzerland) 24 h before transfection and transiently co-transfected using lipofectin (Invitrogen, Carlsbad, CA) with 3 ÎŒg of reporter plasmid, either SP-B luciferase [Yan et al, 1995] or SP-C luciferase plasmid [Kelly et al, 1996]; 2 ÎŒg of mock vector pcDNA3; and wild-type NKX2-1 or mutated NKX2-1 as specified in the figure legends. The cells were co-transfected with pRL-TK (Promega, Madison, WI) to normalize cell transfection efficiency.…”
Section: Cell Culture and Transactivation Experimentsmentioning
confidence: 99%
“…Nuclear proteins were further extracted using the NE-PER nuclear kit (Pierce, Rockford, IL). Two micrograms of nuclear protein extract were mixed with 40 fmol of biotinylated labeled SFTPB (SP-B-f1, [Bohinski et al, 1994]), SFTPC [Kelly et al, 1996], and TG (oligonucleotide C, [Santisteban et al, 1992]) probes (Sigma-Aldrich) derived from the corresponding promoters, as recommended by the manufacturer. For competition incubations, a 100-fold excess of cold probe was used.…”
Section: Emsamentioning
confidence: 99%
“…Restriction of SP-C expression to the lung epithelium is conferred by regulatory elements located within ÏȘ215 bp of the human SP-C promoter (13). This region, which is highly homologous between humans and mice, contains conserved binding sites for thyroid transcription factor 1, a phosphorylated, homeodomain-containing member of the Nkx nuclear transcription factor family (TTF-1; also called Nkx2.1 and T-EBP; mouse genomic designation Titf1) (14). TTF-1 is expressed in the epithelium of the developing lung, thyroid, and in the central nervous system.…”
mentioning
confidence: 99%
“…The CF cuboidal cells of the alveoli were shown to possess characteristics of type II pneumocytes. For example, they exhibited immunoreactivity to TTF-1, a transcription factor that is known to specifically activate genes encoding constituents of surfactant (Bruno et al, 1995;Kelly et al, 1996). They also expressed CK 7, a protein that is found in the alveolar cells (Broers et al 1989;Iyonaga et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To characterize cuboidal alveolar cells, we investigated the expression of proteins evidenced in type II pneumocytes in healthy pulmonary tissue, namely cystic fibrosis transmembrane conductance regulator (McCray et al, 1993;Engelhardt et al, 1994), cytokeratin 7 (Broers et al 1989;Iyonaga et al, 1997), thyroid transcription factor-1 (Bruno et al, 1995;Kelly et al, 1996), as well as cytokeratin 5 a marker of basal and parabasal cells in normal human airway epithelium (Boers et al, 1998) and the Ki-67 antigen, a marker of proliferating cells (Gerdes et al, 1984). The immunohistochemical reactions showed that the alveolar cuboidal cells expressed cystic fibrosis transmembrane conductance regulator (Fig.…”
Section: Cytological Characterization Of Cf Alveoli Before Explantationmentioning
confidence: 99%